A defensin from clam Venerupis philippinarum: Molecular characterization, localization, antibacterial activity, and mechanism of action. Issue 1 (July 2015) - Zhang, Linbao; Yang, Dinglong; Wang, Qing; Yuan, Zeyi; Wu, Huifeng; Pei, Dong; Cong, Ming; Li, Fei; Ji, Chenglong; Zhao, Jianmin
Highlights We cloned a gene of an invertebrate defensin from the clam V. philippinarum. VpDef was constitutively expressed in hemocytes and mantles of the clam. VpDef transcripts were significantly induced after Vibrio anguillarum infection. rVpDef showed the highest activity against Micrococcus luteus. VpDef appears to kill microbes by inducing membrane lesions.